ADHD in children and young people: prevalence, care pathways, and service provision. (February 2018) - Sayal, Kapil; Prasad, Vibhore; Daley, David; Ford, Tamsin; Coghill, David
Summary: Attention-deficit hyperactivity disorder (ADHD) is a common childhood behavioural disorder. Systematic reviews indicate that the community prevalence globally is between 2% and 7%, with an average of around 5%. At least a further 5% of children have substantial difficulties with overactivity, inattention, and impulsivity that are just under the threshold to meet full diagnostic criteria for ADHD. Estimates of the administrative prevalence (clinically diagnosed or recorded) vary worldwide, and have been increasing over time. However, ADHD is still relatively under-recognised and underdiagnosed in most countries, particularly in girls and older children. ADHD often persists into adulthood and is a risk factor for other mental health disorders and negative outcomes, including educational underachievement, difficulties with employment and relationships, and criminality. The timely recognition and treatment of children with ADHD-type difficulties provides an opportunity to improve long-term outcomes. This Review includes a systematic review of the community and administrative prevalence of ADHD in children and adolescents, an overview of barriers to accessing care, a description of associated costs, and a discussion of evidence-based pathways for the delivery of clinical care, including a focus on key issues for two specific age groups—younger children (aged ≤6 years) and adolescents requiring transition of care from child to adult services.